2011
DOI: 10.1002/tee.20654
|View full text |Cite
|
Sign up to set email alerts
|

Development of lateral displacement sensor for real‐time detection of structural damage

Abstract: We have developed a novel sensor that enables us to measure the relative story displacement of a building structure in real time. This lateral displacement sensor (LDS) is composed of a light‐emitting diode (LED) array, which is fixed on the ceiling, and a position‐sensitive detector (PSD) unit, which is placed on the floor. We optimized the LDS to achieve high accuracy in lateral displacement measurement. The accuracy was evaluated to be 60 µm by conducting shaking table tests. Two LDSs were implemented in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…It can be concluded that the precision of the smartphone is lower than Kanekawa et al, 6 Matsuya et al, 7 and Matsuya et al, 8 but higher than Islam et al, 5 and Dai et al 10 The advantages of using a smartphone include the low cost, convenience, and large measurement range. However, they also have a relatively low precision and sampling rate.…”
Section: Sensor Comparisonmentioning
confidence: 95%
See 1 more Smart Citation
“…It can be concluded that the precision of the smartphone is lower than Kanekawa et al, 6 Matsuya et al, 7 and Matsuya et al, 8 but higher than Islam et al, 5 and Dai et al 10 The advantages of using a smartphone include the low cost, convenience, and large measurement range. However, they also have a relatively low precision and sampling rate.…”
Section: Sensor Comparisonmentioning
confidence: 95%
“…4 As these disadvantages impact the ability to accurately monitor displacement, many instruments have been developed to monitor interstory drift directly. These include the laser-based method, 5 a laser light source and phototransistor array, 6 a light-emitting diode array and position-sensitive detector unit, [7][8][9] and consumer grade digital cameras. 10 However, these methods require professional instruments, which significantly affect the cost.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its wider spectral range, higher detection precision, higher response rate and simpler processing circuit, position sensitive detector (PSD) has received extensive attention in recent years and is widely used in a variety of measurement systems [1][2][3][4][5]. Typically the PSD is combined with the laser diode (LD) to detect micro-displacement, which is the so-called LD-PSD triangulation system.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, measuring relative lateral displacement in a building structure has attracted much attention because of its capability for direct damage assessment (Nitta, et al, 2006, Matsuya et al, 2010, 2011. Figure 1 shows relative lateral displacement between a lower floor and an upper floor in a building during an earthquake.…”
Section: Introductionmentioning
confidence: 99%
“…The seismic forces are applied to any vertical position of the building and displace the floors relatively inside the building because each floor is recognized as a concentrated mass. Since permanent deformation of building elements results in residual displacement, a direct displacement measurement method is an even more powerful tool for structural health monitoring compared to the conventional accelerometer which, in principle, cannot follow low-frequency movements (Matsuya, et al, 2011). Also, by combining numerical simulation and real-time lateral displacement information, a precise assessment of a building structure can be given.…”
Section: Introductionmentioning
confidence: 99%